FACTORS THAT AFFECT THE ISLAMIC MORALS OF Y AND Z GENERATION - Pertiwi, Yuarini Wahyu; Febrieta, Ditta; Muminin, Amirul; Ismail, Ismail (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The era of globalization has affected the moral decline in terms of generations. Family, environment, and friends play an essential role as a source of moral knowledge and experience to keep generations out of moral decline. The purpose of the study in this research was to focus on the Islamic morals of Y and Z generations, born in between 1980-1994 and 1995-2009, based on the Ten Commandments written in the Al-Quran Al-Anam [6]: 151-153. This Research used 217 participants (Y generation=67, Z Generation=150). The method of this study used quantitative approach with Islamic moral scale which consists of 26 items. The scale was distributed online by simple random sampling technique. The questionnaire summarized the Ten Commandments into five values - Tauhid, Family, Humanity, Justice, and Honesty - based on cognitive, affective, and behavioral aspects. This study found differences between Islamic morals in Y to Z generations, where Islamic morals declined from Y generation to Z generation. Then, three factors - namely Family, Environment, and Friends - significantly influenced Islamic morals on Z generations. In this regard, the family, followed by peers in succession, played an essential factor in forming individual Islamic morals. In addition, there were differences in Islamic morals between generations.